Reducing the Prevalence of Stunting Rates through the Foster Fathers for Stunting Children Program - Muhammad Ridho Nugroho; Erwin Armeidi; Trisko Defriansya; Henita Andrian; Emra Endi Kesuma; Jeannnita Sri A P; Nurmalina Nurmalina (Indonesian Journal of Health Research and Development, 2023)
Through the foster father program for stunted children, which was started by the Lubuklinggau Mayor, this study seeks to lower the prevalence of stunting in Lubuklinggau City. In October 2023, 155 stunted toddlers were registered in the ePPGBM application. During the intervention period, each child is assigned a foster father who will help by providing meals. By comparing the nutritional status of toddlers before and after receiving assistance from the foster father program for stunting toddlers, this study employed an experimental design. The research method used is an experimental method. The effectiveness of the intervention program provided was then determined using the paired samples T test. The findings indicated that there were significant differences in the nutritional status of toddlers before and after receiving the intervention, with a p-value of 0.000 (.05) and the study's findings indicate that the stunting foster father program had an impact on the nutritional status of the toddlers who received intervention, as evidenced by the 19 toddlers (12.2%).